Advanced Extrauterine Pregnancy at 33 Weeks with a Healthy Newborn. (3rd December 2014) - Dabiri, Tajudeen; Marroquin, Guillermo A.; Bendek, Boleslaw; Agamasu, Enyonam; Mikhail, Magdy
Abstract : Abdominal pregnancy is a very rare form of ectopic pregnancy, associated with high morbidity and mortality for both fetus and mother. It is, and often, seen in poor resource nations, where early diagnosis is often a major challenge due to poor prenatal care and lack of medical resources. An advanced abdominal pregnancy with a good fetal and maternal outcome is therefore a more extraordinary occurrence in the modern developed world. We present a case of an abdominal pregnancy at 33.4 weeks in an individual with no documented prenatal care, who arrived in a hospital in the Bronx, in June 25th 2014, with symptoms of generalized, severe lower abdominal pain. Upon examination it was found that due to category III fetal tracing an emergent cesarean section was performed. At the time of laparotomy the fetus was located in the pelvis covered by the uterine serosa, with distortion of the entire right adnexa and invasion to the right parametrium. The placenta invaded the pouch of Douglas and the lower part of the sigmoid colon. A massive hemorrhage followed, followed by a supracervical hysterectomy. A viable infant was delivered and mother discharged on postoperative day 4.